Principal Component Analysis of morphological traits of synthetic White Leghorn chicken - DALAL, D S; RATWAN, POONAM; MALIK, B S; PATIL, C S; KUMAR, MANOJ (The Indian Journal of Animal Sciences, 2021)
The aim of present study was to assess the relationship among morphological traits and identify the components that define body conformation in a synthetic White Leghorn strain using multivariate procedure principal component analysis. Data were collected from the records of synthetic White Leghorn strain maintained at Poultry Breeding Farm, LUVAS, Hisar. A total of 12 different morphological traits, viz. 40 week body weight, beak length, comb length, keel length, body length, breast girth, breast angle, radius-ulna length, shank length, shank circumference, back length and tail length were recorded and statistical analysis revealed the means for corresponding traits as 1972.65 g, 2.25 cm, 10.74 cm, 12.61 cm, 33.10 cm, 31.40 cm, 55.19 degree, 13.28 cm, 8.37 cm, 4.33 cm, 26.58 cm and 22.94 cm, respectively. Phenotypic correlations among considered body measurements were found to be positive and highly significant varying from 0.394 (breast angle-back length) to 0.965 (body length-back length). All body measurements taken into the study showed high correlation with 40 week body weight indicating the possible use of body measurements in predicting body weight in synthetic White Leghorn strain. The extracted single component explained 75.307% of the total variability in the original parameters and had high loadings for all the considered traits except breast angle. Communality estimates varied from 0.313 (breast angle) to 0.900 (body length) in present study. Further, low communality estimate for breast angle observed in this study indicated that breast angle is frail in elucidating the total variation in body measurements of synthetic White Leghorn strain.